PENGARUH POLA ASUH ORANG TUA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI IPS SMAN 1 RANTAU KOPAR, KABUPATEN ROKAN HILIR - Maharunnisah Maharunnisah; Gimin Gimin; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to know the influence parenting on achievement learn students in a lesson economy class XI IPS SMAN 1 Rantau Kopar, Kab. Rokan Hilir. The population in this research is the class XI IPS 1 and 2 of 51 students and all students become subject of research. Measurement data using questinnaire (Parenting) and documentation (Achievement learning). Data analysis used is multiple linier regression. Based on the results of the descriptive analysis in general parents applying parenting democratic to her son. Achievement learning students in take the value of the original sumatif show only 4 students who complete KKM of 80 the rest not complete value KKM. Furthermore the results of research test the show jointly the influence of positive parenting (Authoritarian attitude, democratic, permissif) against the achievements learn students in the subjects economy class XI IPS SMAN 1 Rantau Kopar, Kab. Rokan Hilir. The magnitude of the influence of variable free against variable tied 46,8% and the rest 53,2% influenced variable other not conscientious. With the equation Y=51,725+0,037X1+4,247X2+1,296X3. So in the hope of the old man students SMAN 1 Rantau Kopar, Kab. Rokan Hilir. Can increase its role for lead her child through the parenting democratic so that the achievements learn students to be better again.Key word : Parenting authoritarian attitude, Democratic, Permissif, Achievement learning